The purification of desire in Dante’s purgatory - Messa Gaya, Patricia (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
Is desire present enough in the Divine Comedy to be taken into consideration? Is the purification of desire really the core of the dantesque Purgatory? With these two questions, we want to illuminate the theme of desire in the dantesque poem. The dissertation will be framed in the sense of desiderium provided by Thomas Aquinas in his Treatise on the passions (S. Th., I-II, q.22-48) and in the questions related to the powers of the soul (S. Th., I, q.78-80). With the thomist framework as a reference, we will study the purification of desire, especially the rational one, and we will understand it as the process of ordering and unveiling man’s ultimate desire: to contemplate God face to face. For this, we will highlight the role of virtue and the education of the gaze as two fundamental factor to complete the ascent up the mountain of purification and allow the soul to reach the summit of its desires in Paradise. In conclusion, we will point out that the purification of desire illuminates our nature and allows us toa chieve the real union between God and his creature.
Keywords: Desire; Purification; Love; Purgatory; Contemplation; Virtue; education